Multilingualism: Its open and hidden agendas - Komorowska, Hanna (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2013)
The author analyses tendencies presented in recently launched EU reports claiming that newly published data reveal a need to rethink approaches to individual and social multilingualism. In the first part of the article approach- es to individual as well as to societal multilingualism are discussed from a historical perspective. In the second part meanings ascribed to the promo- tion of multilingualism are analysed from the language perspective together with the use made of them in the field of social and political activity. Pro- moting multilingualism is then looked at from the perspectives of the learner and the teacher. Implications are finally sought for teaching, learning and assessment in language education.
Keywords: European language policy; assessment; plurilingualism; multilingualism; second language teaching; multilingual teacher; language learning